Vacillation and performance: how alignment with environmental changes drives effective vacillation - Lee, MinJae (Academy of Management Proceedings, 2025)
Keywords: Empirical research; Environmental effect; Mechanism (biology); Period (music); dept.mgt

The Effect of Market-Entry Timing on a Firm’s Speed and Cost of Entry - Lee, Minjae (American Journal of Management, 2023)
This paper examines the effect of market-entry timing on a firm’s speed and cost of entry in a setting where a firm needs to build a plant for market entry. Based on our developed analytical model, we provide seven scenarios of the market-entry timing effect on a firm’s entry speed and cost. We test hypotheses in the liquefied natural gas (LNG) industry. We use Wooldridge’s three-step instrumental variable (IV) approach to account for endogeneity bias. We find that a late entrant has (1) a shorter time-to-build and (2) a higher cost-to-build relative to an early entrant. Further, (3) the late entrant positively moderates the negative relationship of time-to-build and cost-to-build (i.e., the negative relationship of time-to build and cost-to-build becomes less negative for the late entrant). These empirical results are consistent with the prediction of when both revenue effect (i.e., revenue curve shift) and cost effect (i.e., cost curve leftward shift) exist.
Keywords: dept.mgt; peer-reviewed; time compression diseconomies